2017
DOI: 10.1515/amm-2017-0266
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Stability and Selected Mechanical Properties of Zr48Cu36Al8Ag8 Bulk Metallic Glass

Abstract: The aim of this work was to investigate the influence of isothermal annealing on the amorphous structure stability of the Zr 48 Cu 36 Al 8 Ag 8 alloy. A series of continuous heating examinations was performed on the differential scanning calorimeter in order to determine the temperature limits for isothermal annealing series where the time to crystallization was measured. The obtained results were calculated and a time-temperature-transformation diagram was created and discussed. Static compression test as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This can be explained by the fact that the Febased nanocrystalline alloy has a much higher hardness than Zrbased alloy. It is also found that the composite material with the smallest volume ratio of Fe based alloy has a higher hardness (689 HV0.1) than the Zrbased bulk metallic glass with the same chemical composition as that of the Zrbased alloy matrix (614 HV0.1) [30].…”
Section: Fig 2 Xrd Patterns Of the Glassy And Nanocrystalline Powdersmentioning
confidence: 92%
See 1 more Smart Citation
“…This can be explained by the fact that the Febased nanocrystalline alloy has a much higher hardness than Zrbased alloy. It is also found that the composite material with the smallest volume ratio of Fe based alloy has a higher hardness (689 HV0.1) than the Zrbased bulk metallic glass with the same chemical composition as that of the Zrbased alloy matrix (614 HV0.1) [30].…”
Section: Fig 2 Xrd Patterns Of the Glassy And Nanocrystalline Powdersmentioning
confidence: 92%
“…The compression test showed that with increasing of Febased alloy volume ratio up to 40% the fracture strength increases from 1800 MPa corresponding to the Zrbased bulk metallic glass with the same chemical composition as that of the Zrbased alloy matrix [30] to 2369 MPa. Therefore, the presence of the nanocrystalline phase with higher compressive strength than the Zrbased alloy matrix, contributes to the increased compressive strength of the composite material.…”
Section: Fig 2 Xrd Patterns Of the Glassy And Nanocrystalline Powdersmentioning
confidence: 99%
“…The Zr-Cu-Ag-Al system is well known for its excellent glass forming ability [ 2 ]. In particular, the Zr 48 Cu 36 Al 8 Ag 8 alloy exhibits very high crystallization resistance [ 8 ], and thus, it was selected as a substrate material for these studies. Master alloy was prepared by arc melting in an argon atmosphere (5N) with a titanium getter.…”
Section: Methodsmentioning
confidence: 99%
“…These types of surface treatments are usually carried out at elevated temperatures; therefore, their use is inappropriate for processing metallic glasses whose temperature stability is relatively low. However, plasma-assisted methods allow nitriding to be performed at temperatures as low as 573 K (300 °C) and the Zr-based alloys exhibit such high GFA that they can be held and processed around this temperature for many hours [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that some minor additions of silver may increase or decrease the glass forming ability of Zr-Cu-Al alloys depending on the relative amount of these elements [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%